Predicting GPU Performance from CPU Runs Using Machine Learning - Baldini, Ioana; Fink, Stephen J.; Altman, Erik (Anais do International Symposium on Computer Architecture and High Performance Computing (SBAC-PAD), 2014)
Graphics processing units (GPUs) can deliver considerable performance gains over general purpose processors. However, GPU performance improvement vary considerably across applications. Porting applications to GPUs by rewriting code with GPU-specific languages requires significant effort. In consequence, it is desirable to predict which applications would benefit most before porting to the GPU. This paper shows that machine learning techniques can build accurate predictive models for GPU acceleration. This study presents an approach which applies supervised learning algorithms to infer predictive models, based on dynamic profile data collected via instrumented runs on general purpose processors. For a set of 18 parallel benchmarks, the results show that a small set of easily-obtainable features can predict the magnitude of GPU speedups on two different high-end GPUs, with accuracies varying between 77% and 90%, depending on the prediction mechanism and scenario. For already-ported applications, similar models can predict the best device to run an application with an effective accuracy of 91%.